Higher banknotes and inflation: A myth or a reality? Evidence from Syria - Al-Ahmad, Zeina; Ismaiel, Linda Ali (The Economics and Finance Letters, 2025)
Before the onset of the Syrian crisis in 2011, the exchange rate of the Syrian pound (SP) to the USD was SP45 to USD1. The Syrian pound kept depreciating until it reached SP3500 to USD1 in 2021. The constant depreciation in the value of the Syrian pound led to unprecedented high levels of inflation. This pushed the monetary authorities to introduce higher banknotes, the SP2000 and the SP5000 to facilitate the conduct of daily transactions. The issuance of higher banknotes triggered public concerns regarding the inflationary impact of these banknotes. Moreover, rumors are now circulating that the SP10000 note has already been printed and will be put into circulation soon to address the constant depreciation of the Syrian pound (SP15000=USD1 in 2024). This study aims at investigating the impact of higher banknotes on the level of inflation in Syria between 2011 and 2021. The study utilized structural break tests such as the Zivot and Andrews and the Lee and Strazicich to examine whether putting higher banknotes into circulation led to structural breaks in the series of inflation. The results obtained conclusively revealed that putting higher banknotes into circulation did not cause a structural break in the series of inflation. Accordingly, the findings cannot support the view that issuing higher banknotes leads to higher inflation. This implies that the monetary authorities in Syria should not keep postponing the issuance of higher banknotes out of inflationary concerns.